Caracterização comportamental das feições erosivas na Bacia do Córrego Campo Alegre com base nos estudos geológico-geotécnicos: perímetro urbano de Uberlândia - MG - Giffoni, Sara Nunes (2010)
The meaning of this work is to characterize the erosion feature at Campo Alegre stream, trough geological and geotechnical by categorizing essais the physical environment attributes and determining geotechnical parameters and also geoprocessing to be possible match this analysis and get to the factor of development and evolution of erosion.This research is justified by the similar situation at several streams in Uberlândia, both erosive processes as landscape configuration process. Were produced 4 soil profiles and in each 5 soil levels, except profile number 3 with 3 levels. From these 4 profiles, were taken several disturbed and undisturbed samples and made the following essays: Granulometria, Limites de Atterberg, Permeabilidade in situ, adensamento, cisalhamento, erodibilidade and adsorção de azul de metileno. Were prepared hypsometric maps and slope maps, produced based on the topographic map.Results showed that the soil is silty-sand and with low cohesion, therefore loses more easily the soil of lowest levels of the profiles. The highers levels are less erodible and get easily amount cause of organic materials, thus acquire a greater aggregation and yield and lack of bases being transported by the stream. The destination of rain water coming from the neighborhoods in the headwaters of streams, enhances the water volume in the channel by the increasing os mechanical action of water that has a large power on carring materiais used to backfill the erosion. In the medium course of the stream right arm channel has a meandering course to the right and due to the transportation of lowest levels and bases it has started a piping process and collapse on the surface by the lackinf of support, characterizing this area as the highest intensity of erosion.The blocks keep falling depositing more material to be transported as the next rainy season and again release the latest levels to be removed by pipping.